La participación de los candidatos a la Alcaldía de Loja en el debate obligatorio dispuesto por el Consejo Nacional Electoral, previo a las últimas elecciones seccionales de febrero de 2023 y su incidencia en los electores mayores de 30 años de la parroquia urbana El Sagrario del cantón Loja, provincia de Loja - Orellana Jiménez, Juliana del Cisne (2024)
Electoral debates in Ecuador have become the space where candidates present their proposals, ideas and work actions. The objective of this research was to determine if the debates promoted by the National Electoral Council (CNE) influenced citizens to opt for a particular candidate, as well as to determine if the questions asked to the candidates for mayor of Loja during the electoral debate were in accordance with the local reality for voters to know the proposals and work plans of the candidates; and to know if the preferences of voters were modified after listening to the proposals and work plans of the candidates for mayor of Loja, during the electoral debate. The methodology used contemplated the application of surveys and interviews as part of the field work, with the participation of voters, candidates and analysts, which allowed fulfilling the main objective of the research; and also accessed information provided by the provincial delegation of the National Electoral Council. In this way, results were obtained for the respective quantitative and qualitative analysis; among the main findings it was possible to establish that 28.30% and 9.90% of the surveyed voters responded that they agreed and completely agreed, respectively, that the debate did influence their vote in the election of mayor in the February 2023 elections. However, two groups with similar percentages (21.30% and 20.10%) expressed that it was indifferent and that they disagreed with respect to its influence. On the other hand, the experts interviewed do not consider that the debate had a significant influence on the citizens' voting decision. They argue that the participation of several candidates generated confusion and dispersed votes, which meant that the debate was not a determining factor. In addition, it was established that the majority of citizens agreed with the methodology and the topics proposed in the electoral debates. However, candidates and analysts expressed that the time of intervention in the debates was limited due to the proposed methodology and the large number of candidates who participated, which prevented them from presenting their work plans in a complete and well-founded manner. Based on these findings, an analysis was carried out that included the review and contrast of relevant concepts of the research, and finally the corresponding conclusions and recommendations were presented.